Systemic and cerebral exposure to and pharmacokinetics of flavonols and terpene lactones after dosing standardized Ginkgo biloba leaf extracts to rats via different routes of administration. (27th August 2013) - Chen, Feng; Li, Li; Xu, Fang; Sun, Yan; Du, Feifei; Ma, Xutao; Zhong, Chenchun; Li, Xiuxue; Wang, Fengqing; Zhang, Nating; Li, Chuan
Abstract : Background and Purpose: Flavonols and terpene lactones are putatively responsible for the properties of Ginkgo biloba leaf extracts that relate to prevention and treatment of cardiovascular disease and cerebral insufficiency. Here, we characterized rat systemic and cerebral exposure to these ginkgo compounds after dosing, as well as the compounds' pharmacokinetics. Experimental Approach: Rats received single or multiple doses of ShuXueNing injection (prepared from GBE50 for intravenous administration) or GBE50 (a standardized extract of G. biloba leaves for oral administration). Brain delivery of the ginkgo compounds was assessed with microdialysis. Various rat samples were analysed using liquid chromatography/mass spectrometry. Key Results: Slow terminal elimination features of the flavonols counterbalanced the influence of poor oral bioavailability on their systemic exposure levels, which also resulted in significant accumulation of the compounds in plasma during the subchronic treatment with ShuXueNing injection and GBE50. Unlike the flavonols, the terpene lactones had poor enterohepatic circulation due to their rapid renal excretion and unknown metabolism. The flavonol glycosides occurred as major forms in plasma after dosing with ShuXueNing injection, while the flavonol aglycone conjugates were predominant in plasma after dosing with GBE50. Cerebral exposure was negligible for the flavonols and low for the terpene lactones. Conclusion and Implications: Unlike the significant systemic exposure levels, the levels of cerebral exposure to the flavonols and terpene lactones are low. The elimination kinetic differences between the two classes of ginkgo compounds influence their relative systemic exposure levels. The information gained is relevant to linking ginkgo administration to the medicinal effects.